A study of certain motivational characteristics in karate-do: the case of the national elite - benhamed, noureddine (sports creativity, 2025)
The topic of motivation has attracted the attention of many researchers and scholars of human behavior, who have attempted to uncover the essence and meaning of motivation, given its paramount importance in driving individuals to strive for the best and, in many cases, to raise the bar in order to achieve the best possible outcomes and the highest levels of performance. Undoubtedly, the topic of motivation in sports has also received a lot of attention from sports psychologists in particular, as it is a decisive factor for both coaches and athletes alike, since it is considered one of the factors that may contribute in one way or another to raising the level of athletic achievement and thus reaching better levels. Through this approach, this study, in both its theoretical and fieldwork aspects, attempts to answer a series of questions that we summarize in the following two questions: - Do the motivational characteristics of karate athletes differ according to their personal characteristics? (age, educational level, rank, seniority in practice, competitive level, gender). What are the levels of motivation among Algerian national elite karate athletes? Keywords: motivation, trait, karate